Research progress on the improvement of electrode lifespan of spot welding for aluminum alloy - Xiaoqian PAN; Pengpeng LIU; Lin LUO; Qingwei BAI; Miaojin QU; Xiaoling WANG; Shengxiang LIU (Hanjie xuebao)
Resistance spot welding (RSW) of aluminum alloys is one of the critical welding processes in the manufacturing of new energy vehicles, with widespread applications and significant importance. However, severe electrode wear and a high frequency of reconditioning are the main challenges for RSW of aluminum sheets. These issues not only lead to increased manufacturing costs but also affect production efficiency, becoming a major factor constraining production pace. Due to the high thermal conductivity and good electrical conductivity of aluminum alloys, RSW of aluminum typically employs high current and short-time, which cause severe electrode burning under high temperature and pressure. Additionally, the high-melting-point alumina film on the surface of the aluminum sheet is detrimental to the optimal bonding between the electrode and the aluminum sheet. Therefore, reducing electrode wear in aluminum RSW and extending the service life of electrode caps are urgent problems requiring solutions. The failure modes and mechanisms of electrodes in aluminum RSW are reviewed. The technical approaches to improve the lifespan of aluminum RSW electrodes are systematically discussed from the perspectives of electrode materials, electrode surface modification, electrode structure design, aluminum sheet surface treatment, and welding processes. It provides important guidance and reference for related producers and users.